What Makes a Mound? Earth-Sourced Materials in Late Iron Age Burial Mounds. Issue 4 (November 2021) - Cannell, Rebecca J.S.
Abstract : The interpretation of Late Iron Age burial mounds often focuses exclusively on the discovered contents, the social identity or role of the interred and the economic and political implications that can be extracted. This article considers the mound itself as a basis for archaeological interpretation, and attempts to place substantial late Iron Age burial mounds within the landscape they are made of. Within these burial mounds internal references to time, place and the transformations and imbued associations within the earth-sourced materials are purposeful and significant. This is illustrated via comparable examples from southern Norway, and to add contrast, cases from the Viking Age Isle of Man will be explored. This article will outline why the selected mounds should be seen as closely related to each other in the references they contain, and how the materials used can be seen as a purposeful link to the land itself.